2009
DOI: 10.1136/bmj.a3064
|View full text |Cite
|
Sign up to set email alerts
|

Effect of peer support on prevention of postnatal depression among high risk women: multisite randomised controlled trial

Abstract: Objective To evaluate the effectiveness of telephone based peer support in the prevention of postnatal depression.Design Multisite randomised controlled trial.Setting Seven health regions across Ontario, Canada.Participants 701 women in the first two weeks postpartum identified as high risk for postnatal depression with the Edinburgh postnatal depression scale and randomised with an internet based randomisation service.Intervention Proactive individualised telephone based peer (mother to mother) support, initi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

24
474
4
14

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 377 publications
(535 citation statements)
references
References 69 publications
24
474
4
14
Order By: Relevance
“…209 The remaining 6 of 10 studies reported on weight change from prepregnancy weight to postpartum weight measured at time points ranging from 6 months to 8 years postpartum. 204,206,[217][218][219]221 Of these, 3 reported no statistically significant differences, 204,206,217 and 1 reported a difference only for the group with the longest period of exposure (20 weeks or more). 221 Two studies, set in the United States, reported differences by exposure.…”
Section: Durationmentioning
confidence: 99%
See 3 more Smart Citations
“…209 The remaining 6 of 10 studies reported on weight change from prepregnancy weight to postpartum weight measured at time points ranging from 6 months to 8 years postpartum. 204,206,[217][218][219]221 Of these, 3 reported no statistically significant differences, 204,206,217 and 1 reported a difference only for the group with the longest period of exposure (20 weeks or more). 221 Two studies, set in the United States, reported differences by exposure.…”
Section: Durationmentioning
confidence: 99%
“…221 Two studies, set in the United States, reported differences by exposure. Specifically, 1 study reported a lower risk of weight retention of 20 pounds or more among those who partially or exclusively breastfed for 6 months or more when compared with those who did not, 219 and a second reported lower weight retention among those who were still breastfeeding at 6 months postpartum compared with those who were not. 218 …”
Section: Durationmentioning
confidence: 99%
See 2 more Smart Citations
“…Un soutien des paires sous forme d'appui téléphonique, en augmentant la confiance en elles des mères, permet parfois d'améliorer la durée et l'exclusivité de l'allaitement maternel [41].…”
Section: Facteurs Liés à L'entourageunclassified